Study of the effect of pulse plating parameters on the electrodeposition of NiP and NiP/SiC coatings and their microhardness values. (2nd January 2021) - Ahmadkhaniha, D.; Tsongas, K.; Tzetzis, D.; Zanella, C.
ABSTRACT: This study is focused on finding optimised conditions for electrodeposition of NiP and NiP/SiC coatings, which enhance the coatings' microhardness. Both the effect of particles and the effect of heat treatment at 400°C for 1 h on the microhardness of the coating were studied. The effects of pulse electrodeposition parameters including duty cycle, frequency, and peak current density on the composition of NiP and NiP/SiC composite coatings were examined, and the results were compared with those from direct current plating. Pulse plating increased the current efficiency of NiP deposition while decreasing the phosphorus content of these coatings in comparison to direct plating, resulting in higher microhardness values. It was also shown that wt.%P in NiP coating depends not only on peak current density but also on bath charge of pulse plating. Pulse plating parameters (duty cycle and frequency) and the low incorporation of SiC particles did not affect microstructure or the microhardness of the coatings, while heat treatment was the main factor that increased microhardness.